2001
DOI: 10.1093/humrep/16.12.2606
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome and the risk of spontaneous abortion following assisted reproductive technology treatment

Abstract: The results of this study suggest that the higher risk of spontaneous abortion observed in women with PCOS is likely to be due to their high prevalence of obesity and the type of treatment they receive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
2
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(115 citation statements)
references
References 16 publications
4
98
2
11
Order By: Relevance
“…We speculate that this could be due to poorer embryo competence in the PCOS group which might have offset the positive effect from the quantitative aspect. Actually it has been reflected in terms of higher miscarriage rates in the PCOS group compared to the isolated PCO and control groups, both from our findings as well as those reported by some others [12,20]. It was suggested that this increased miscarriage rate in PCOS was not explained genetically by increased risk of embryonic aneuploidy [21].…”
Section: Discussionsupporting
confidence: 83%
“…We speculate that this could be due to poorer embryo competence in the PCOS group which might have offset the positive effect from the quantitative aspect. Actually it has been reflected in terms of higher miscarriage rates in the PCOS group compared to the isolated PCO and control groups, both from our findings as well as those reported by some others [12,20]. It was suggested that this increased miscarriage rate in PCOS was not explained genetically by increased risk of embryonic aneuploidy [21].…”
Section: Discussionsupporting
confidence: 83%
“…Wang et al found that a higher rate of spontaneous miscarriage in PCOS patients was due to higher prevalence of obesity [11]. In addition, Boots et al found that obese women are more prone to have euploid miscarriage compared to non-obese controls [12].…”
Section: Discussionmentioning
confidence: 99%
“…Glycodelin may play a role in inhibiting the endometrial immune response to the embryo and IGF binding protein-1 appears to facilitate adhesion processes at the feto-maternal interface. 35,36 Multiple studies have documented the link between high BMI and higher fetal loss rate, 22 probably linked to a higher insulin resistance among these obese women. Although many women with PCOS are obese, obesity is not a part of the diagnostic criteria for PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…3 During the last decade, several retrospective and nonrandomized studies have evaluated metformin for its potential disease-modifying effects. Studies have shown that without metformin, spontaneous abortion may occur in 25% to 73% [21][22][23] of pregnancies than the general population. The increased risk may be due to hyperandrogenism, high LH level, more insulin resistance and higher levels of plasminogen activator inhibitor activity (PAI-1) which adversely affects endometrial function and environment.…”
Section: Introductionmentioning
confidence: 99%